2016
DOI: 10.1128/aac.00269-16
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Plasmid-Mediated Colistin Resistance Gene mcr-1 in a Clinical Escherichia coli Isolate from Egypt

Abstract: C olistin is considered a last resort for the treatment of infections caused by carbapenemase-producing members of the family Enterobacteriaceae. Recently, a transferable plasmid conferring resistance to colistin was discovered in Escherichia coli and Klebsiella pneumoniae from China (1) and was then reported in various bacteria from many other countries (2-4). This spread of antibiotic resistance heralds a return to the preantibiotic era, especially with no new antibiotics in the pipeline. The plasmid-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 9 publications
2
58
2
1
Order By: Relevance
“…Similarly, ST167 and ST410 carried bla CMY in addition for cephalosporin resistance which was not seen in ST131 and ST405. Recently, plasmid-mediated colistin resistance is being increasingly reported in E. coli [32][33][34]. This study also observed two isolates (B7532, B9021) with mcr-1.1 expressing high MIC of >32 μg/ml to colistin and both the isolates, from the same time period and ward, were closely related with same sequence type (ST624).…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, ST167 and ST410 carried bla CMY in addition for cephalosporin resistance which was not seen in ST131 and ST405. Recently, plasmid-mediated colistin resistance is being increasingly reported in E. coli [32][33][34]. This study also observed two isolates (B7532, B9021) with mcr-1.1 expressing high MIC of >32 μg/ml to colistin and both the isolates, from the same time period and ward, were closely related with same sequence type (ST624).…”
Section: Discussionsupporting
confidence: 68%
“…23,25 In addition, clinical isolates that contain the mcr-1 gene have been reported in Vietnam, China, Taiwan, Thailand, Laos, Cambodia, the Netherlands, Sweden, the UK, Germany, Denmark, Switzerland, Italy, South Africa, Egypt, Argentina and the United States. 23,[25][26][27][28][29][30] Of interest, Shen and colleagues 31 showed the presence of mcr-1 in 3 E. coli isolates of chicken origin from China dating back to the 1980s, which supports the view that this is not a new resistance mechanism despite its recent recognition. The mcr-1 gene has been found most commonly in E. coli but has also been detected in Salmonella spp.…”
Section: Discussionmentioning
confidence: 91%
“…The conventional way to cure bacteria infections is the use of antibiotics, but the efficiency of antibiotics is threatened by the increased antibiotic resistance of bacteria . For instance, the superbug E. coli bacteria with mcr‐1 gene is resistant to colistin, an antibiotic which is the last choice for treating multidrug‐resistant (MDR) bacterial infections . The increasing emergence of MDR bacteria not only caused the failure of antibiotic treatment but also aggravated the economic burden of the patients due to the prolonged hospitalizations .…”
Section: Introductionmentioning
confidence: 99%